Exploring AI Applications in Curriculum Customization: Best Practices and Case Studies - Ahmad, Biamin; Sharin, Farah Hida; Bahadin, Siti Azura; Balbir Singh, Harjinder Kaur; Mohd Razali, Muhamad Faizzuddin; Ab Ghani, Muhamad Amin; Abbas, Mohd Saleh (SEEJPH, 2025)
This review article explores the integration of Artificial Intelligence (AI) in curriculum customization, focusing on best practices and practical case studies from educational institutions worldwide. AI technologies, such as adaptive learning systems, intelligent tutoring systems, and data-driven analytics, have significantly impacted curriculum design and delivery. The paper reviews recent applications from 2013-2024, illustrating how AI is used to create personalized learning paths, enhance student engagement, and improve educational outcomes. Through case studies from various regions, we analyze the effectiveness, challenges, and ethical considerations of AI in curriculum customization, offering valuable insights for educators, policymakers, and educational technology developers.